An Integrated Optimization Approach of p-Hub Median Problem and Service Facility Configuration. Issue 1 (October 2020) - Yu, Wang; Shilin, Yan; Tong, Che; Tong, Chen
Abstract: Traditional network design approach neglected the impact of network-wide location of service facility configuration on hub network designing scheme. In order to improve the mutual adaptability between hub network scheme and service facility configuration, the selections including the location of hubs, the itinerary of OD pairs and the allocation of both types and number of service facilities on each link were considered as the decision variables. The limitations of the maximum expected number of service facilities deploying on each link and the total service time of each facility type were treated as constraints. Then an integrated mathematical model of p -hub median problem and service facility configuration was constructed. A numeric example with the scale of 9 cities, 4 types of aircraft and 72 OD pairs in domestic airline industry in 2016 is used to verify the feasibility. The results indicate that the approach can decrease the hub network designing cost by 1.34% and the adaptability of hub network scheme to service facility configuration is significantly raised as compared to the traditional approach.